Dampak brand experience terhadap brand attachment: Brand trust sebagai mediator - Muhammad Gaudi Ilyasa; Lisa Jolanda Catherine Polimpung; Fransisca Mulyono (Universitas Kristen Maranatha, 2025)
This study aims to evaluate the influence of brand experience on brand attachment, both directly and indirectly through brand trust. A total of 150 respondents were selected using a non-probability sampling method with a purposive sampling technique, consisting of consumers of Pipinos Bakery. The sampling method used in this research was non-probability sampling with a purposive sampling technique, targeting consumers of Pipinos Bakery. The researcher conducted the study using an outer model evaluation, namely validity and reliability tests, and an inner model evaluation, including the coefficient of determination (R²), predictive relevance (Q²), path coefficient significance (two-tailed), and effect size (f²). The analysis was carried out using SEM PLS 3.0 software to obtain accurate results. The findings show that brand attachment is significantly influenced by brand experience, both directly and through brand trust as a mediating variable. These results suggest that Pipinos Bakery needs to enhance the brand experience perceived by consumers to strengthen both brand trust and brand attachment. Several strategies to improve brand experience include providing sampling corners for new products, greeting consumers by name to create a more personal impression, offering loyalty programs such as coupons, and providing special offers on birthdays or custom product options. These efforts will help Pipinos Bakery navigate business competition in the current era.